Everyday practices in the production of uneven water pricing regimes in Lilongwe, Malawi. (March 2021) - Pihljak, Lejla H; Rusca, Maria; Alda-Vidal, Cecilia; Schwartz, Klaas
Recent scholarship has called for widening investigations of cities through the analysis of everyday practices that shape urban life. Critical water studies have contributed to this emerging debate by using an everyday lens to document the diversity of practices of accessing and distributing water. Thus far, little attention has been given to the everyday practices of setting water prices and how these shape access. We contribute to this gap by investigating the practices of setting prices in two distinct service modalities within Lilongwe's water supply network. Our study reveals the hybrid and dynamic arrangements that shape pricing regimes, formed through the formal and informal negotiations on subsidies, incentives, tariff increases and distribution of profits. In these negotiations, the decision makers opportunistically mobilise their different and at times conflicting mandates (business and social) and guiding principles (equity versus cost-recovery). We conclude that pricing regimes are the outcome of intertwined structural processes and everyday practices that exacerbate uneven water flows in the city.